Single-Dose Amphetamines in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The efficacy and time course of single morning doses of Adderall®, extended-release (Spansules), and immediate-release (tablets) dextroamphetamine sulfate (DXA) and placebo were compared in 35 children with attention-deficit/hyperactivity disorder (ADHD) in a randomized, double-blind, crossover study at the Child Psychiatry Branch, National Institute of Mental Health, Bethesda, MD.